Zinc negative electrode modified by in-situ chemical crosslinking interface layer as well as preparation method and application of zinc negative electrode

The zinc negative electrode is modified by in-situ chemical crosslinking of sodium alginate interface layer, which solves the problems of zinc electroplating/peeling efficiency and cycle stability, and achieves excellent cycle stability and anti-zincity of zinc negative electrode and water-based zinc-based energy storage devices. Crystal capability.

CN119517923APending Publication Date: 2025-02-25ZHONGYUAN ENGINEERING COLLEGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411424435.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

In the negative electrode side of zinc metal in water-based zinc energy storage devices, there are serious parasitic side reactions when the electrochemical reaction occurs at the electrode interface, resulting in poor zinc plating/peeling efficiency and cycle stability, and uneven zinc deposition morphology, resulting in zinc dendrites. It can affect the long-term stability of the device.

Method used

The zinc negative electrode is modified by in-situ chemically cross-linked sodium alginate (SA) interface layer, and the SA cross-linking polymerization is promoted through La3+ to form a three-dimensional web cage structure, which improves the water resistance and zinc dendrites resistance of the interface layer.

Benefits of technology

The water resistance of the sodium alginate gel coating on the surface of the zinc negative electrode is significantly improved, the growth of zinc dendrites is inhibited, and the long-term good ion migration behavior is maintained, and the excellent cycle stability of zinc negative electrodes and water-based zinc-based energy storage devices is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119517923A_ABST
    Figure CN119517923A_ABST
Patent Text Reader

Abstract

The invention provides an in-situ chemical crosslinking interface layer modified zinc negative electrode and a preparation method and application thereof, and the preparation method comprises the following steps: fully grinding and mixing a lanthanum metal salt and a binder, uniformly coating the surface of the zinc negative electrode with the mixed powder obtained by grinding under the assistance of an organic solvent, and drying to obtain a lanthanum metal salt coating modified zinc negative electrode; and uniformly coating the lanthanum metal salt coating modified zinc negative electrode sheet with the sodium alginate aqueous solution precursor, and drying to obtain the in-situ chemical crosslinking interface layer modified zinc negative electrode containing lanthanum ions and sodium alginate. La3 + is adopted to trigger cross-linking polymerization of sodium alginate, a multifunctional organic-inorganic gel interface layer is formed, the synergistic effect of sodium alginate and La3 + can be fully played, the gel interface layer has the advantages of high stability and interface side reaction inhibition of the gel interface layer, La3 + is introduced into the gel interface layer in situ due to the fact that La3 + initiates cross-linking polymerization of sodium alginate, and the stability of the gel interface layer is improved. And uniform electric field regulation and control are realized. The composite interface layer prepared by the method can prevent corrosion of zinc metal, reduce the hydrogen precipitation tendency of a zinc / electrolyte interface and inhibit zinc dendrites, and the zinc metal negative electrode and the water-based zinc-based energy storage device which can stably operate for a long service life are obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of new energy technology and relates to a zinc negative electrode modified with an in-situ chemical cross-linking interface layer and a preparation method and application thereof. Background Art

[0002] With the increasing prominence of energy consumption and environmental issues, it is of great significance to build a reliable and effective electric energy storage system and utilize renewable and clean energy. Aqueous zinc-based energy storage devices are considered to be one of the most promising candidate systems for the next generation of large-scale energy storage systems due to their low cost, good inherent safety, and suitable redox potential of zinc. However, one of the most difficult challenges of aqueous zinc-based energy storage devices is that the zinc metal negative electrode side is accompanied by serious parasitic side reactions (zinc metal corrosion and hydrogen evolution) when the electrochemical reaction occurs at the electrode interface, which leads to poor efficiency and cycle stability of zinc plating / stripping. In addition, the deposition morphology of zinc will also affect the cycle stability of zinc-based energy storage devices. For example, the zinc deposition environment on the surface of pure zinc negative electrode is uneven, resulting in severe zinc dendrites. These zinc dendrites will lead to the generation of "dead zinc", reduce the efficiency and utilization of zinc, and aggravate the unevenness of the surface of the zinc negative electrode, leading to the growth of vertical dendrites, which may pierce the diaphragm in severe cases, causing battery damage. At present, people have proposed a variety of interface optimization strategies such as designing new zinc anode structures, constructing artificial protective layers, and optimizing electrolyte components. The interface protection layer has the advantages of stability and simple operation. The gel interface layer has good stability and three-dimensional network structure, and people are paying attention to its application in the zinc negative electrode interface layer. Moreover, the gel interface layer can not only solve the problems of inhibiting interface side reactions and zinc dendrites, but also has broad prospects in the fields of flexible wearable devices, flexible energy storage devices, and wide temperature range energy storage systems.

[0003] Sodium alginate (SA) is a cheap raw material for gelation and has good biocompatibility, but the zinc electrode directly modified with sodium alginate has poor water resistance, which affects the battery performance of zinc batteries. Summary of the invention

[0004] In view of the above technical problems, the present invention proposes a zinc negative electrode modified with an in-situ chemical cross-linked interface layer and its preparation method and application. The zinc negative electrode is modified with an in-situ chemical cross-linked sodium alginate (SA) interface layer. 3+ It triggers SA cross-linking polymerization, turning the original one-dimensional chain into a three-dimensional cage, thereby improving the water resistance of the sodium alginate gel coating on the zinc negative electrode surface and inhibiting zinc dendrites. The composite interface layer can maintain the good flexibility and three-dimensional network structure of the gel and maintain long-term good ion migration behavior. It can also be due to La 3+The chemical crosslinking of SA is triggered so that the interface layer has the advantages of both organic matter (good toughness and good water absorption) and inorganic matter (improved hardness and electric field regulation), is not easy to break, and is more stable. Therefore, the zinc negative electrode modified by the in-situ chemical crosslinking interface layer of the present invention exhibits excellent interface stability and long-term cycle stability of the device due to the in-situ chemical crosslinking interface of the organic-inorganic composite.

[0005] In order to achieve the above object, the technical solution of the present invention is achieved as follows: A method for preparing a zinc negative electrode modified with an in-situ chemical cross-linking interface layer, characterized in that the preparation steps are as follows: (1) fully grinding and mixing a lanthanum metal salt and a binder, and uniformly coating the mixed powder obtained by grinding on the surface of a zinc negative electrode with the aid of an organic solvent I, and drying to obtain a zinc negative electrode modified with a lanthanum metal salt coating; (2) The sodium alginate aqueous solution precursor is uniformly coated on the zinc negative electrode sheet modified with the lanthanum metal salt coating, and the trivalent lanthanum ions induce a chemical cross-linking reaction of the sodium alginate. After drying, a zinc negative electrode modified with an in-situ chemical cross-linking interface layer containing lanthanum ions and sodium alginate is obtained.

[0006] Preferably, the metal salt of lanthanum in step (1) is one or more of lanthanum nitrate, lanthanum chloride and lanthanum acetate; the binder is polyvinylidene fluoride or polytetrafluoroethylene, and the organic solvent is.

[0007] Preferably, in step (1), the mass ratio of the lanthanum metal salt to the binder is (9-4):1.

[0008] Preferably, the thickness of the lanthanum metal salt coating on the zinc negative electrode sheet in step (1) is 50-100 μm.

[0009] Preferably, the drying temperature in step (1) is 35-75° C. and the drying time is 4-10 h.

[0010] Preferably, the concentration of the sodium alginate aqueous solution in step (2) is 10-30 mg mL -1 .

[0011] Preferably, in step (2), the scraping thickness ratio of the sodium alginate coating to the lanthanum metal salt coating is (1-3):1.

[0012] Preferably, in step (2), the drying temperature is 30-70° C. and the drying time is 7-10 h.

[0013] Preferably, the zinc negative electrode prepared by the above method is modified with an in-situ chemical cross-linking interface layer.

[0014] Preferably, the application of the zinc negative electrode modified with the in-situ chemical cross-linking interface layer in an aqueous zinc-based energy storage device exhibits excellent long-cycle stability when applied to an aqueous zinc-based energy storage device.

[0015] This method uses La 3+ Triggering the cross-linking polymerization of sodium alginate to form a multifunctional organic-inorganic gel interface layer can give full play to the interaction between sodium alginate and La 3+ The synergistic effect of La 3+ Initiate cross-linking polymerization of sodium alginate to 3+ In situ introduction into the gel interface layer to achieve uniform electric field regulation. The composite interface layer prepared by this method can prevent the corrosion of zinc metal, reduce the tendency of hydrogen precipitation at the zinc / electrolyte interface, and inhibit zinc dendrites, thereby obtaining a zinc metal negative electrode and an aqueous zinc-based energy storage device that can operate stably for a long life. The raw materials used in the zinc negative electrode modified with the in-situ chemical cross-linking interface layer prepared by the present invention are low in cost, the interface layer is continuous, and the adjustability is strong.

[0016] The present invention has the following beneficial effects: 1. The in-situ chemical cross-linking interface layer of the present invention has excellent electrochemical corrosion protection and guides the uniform deposition of zinc ions. In the zinc sulfate electrolyte system, zinc ions are clustered by water molecules, and ordinary zinc sheets form a Gouy-Chapman-Stern model due to the effect of a double electron layer, which makes it difficult for zinc ions to migrate. The chemical cross-linking interface layer has rich and uniform oxygen-containing functional groups and linear chain molecular channels, which promotes the uniform migration of zinc ions. The trivalent lanthanum ions contained inside guide the zinc ions to a certain extent. The dense three-dimensional network structure at the zinc anode interface can greatly reduce electrochemical corrosion while guiding deposition. At the same time, the lanthanum ions promote the three-dimensional cross-linking of sodium alginate, which greatly reduces the swelling reaction of organic matter in the zinc sulfate aqueous solution, while ensuring the functionality and uniformity of the linear organic molecular chain. The linear molecular chain itself only has the effect of uniform deposition, so it promotes the uniform deposition of zinc ions from top to bottom. Therefore, the chemically cross-linked interface layer has the advantages of guiding directional deposition, reducing hydrogen evolution reaction, preventing electrochemical corrosion, and inducing uniform and dense zinc deposition, thereby realizing the development of zinc negative electrodes and zinc ion batteries with long cycle life.

[0017] 2. The present invention achieves the purpose of optimizing the modification of the zinc negative electrode by constructing an in-situ cross-linked chemical interface layer on the Zn electrode and forming a three-dimensional network through three-dimensional cross-linking of lanthanum ions. The membrane has good adaptability to the volume expansion during zinc electroplating / stripping, and the characteristics of its internal water-locking network make the zinc negative electrode have better corrosion resistance and the effect of inhibiting zinc dendrite reaction.

[0018] 3. The cross-linked interface layer prepared by the present invention was applied to an aqueous zinc ion battery. By comparing it with the control sample (blank pure zinc negative electrode), it was found that the electrode surface of the cross-linked interface layer prepared by the present invention was flat before and after the reaction, and no vertical dendrites were found, while the blank pure zinc negative electrode had more vertical dendrites after the reaction, and the negative electrode surface was broken. This confirms that the cross-linked interface layer prepared by the present invention effectively inhibits the growth of zinc dendrites (such as Figure 1 as shown).

[0019] 4. By testing the chemical cross-linked interface layer prepared by the present invention and the comparative sample CA test, it is found that the chemical cross-linked interface layer has excellent performance in ion three-dimensional diffusion due to the rich three-dimensional linear molecular channels and top-down directional deposition guided by oxygen-containing functional groups. This shows that La-SA / Zn has an excellent protective effect on zinc negative electrode deposition and inhibits the generation of dendrites. This shows that the composite material has good structural stability (such as Figure 4 as shown).

[0020] 5. According to the data and performance diagrams given by the present invention, it can be seen that at an area capacity of 1 mAh cm -2 2 mA cm -2 At a current density of 100000 h, the blank pure Zn / / Zn symmetric battery had a sudden drop in polarization voltage after 50 h of cycling, which may be caused by battery short circuit. In addition, in contrast, the chemically cross-linked interface layer anode of the present invention still showed a stable polarization voltage curve after 1400 h of cycling, showing the best cycle stability. It can be seen from the given rate performance diagram that when the switching current density is from 1 to 10 mA cm -2 When the switching current density is from 1 to 10 mA cm, the pure Zn symmetric battery shows a sharp voltage short circuit phenomenon, while the chemically cross-linked interface layer anode has a high switching current density from 1 to 10 mA cm -2 When the -2 Switch back to 1 mA cm -2 When the La-SA / Zn symmetric battery still maintains a stable polarization voltage, it indicates that the chemically cross-linked interface layer anode has excellent rate performance (such as Figure 2 , Figure 5 as shown). BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0022] Figure 1The figures are comparison diagrams of the electron microscope photographs of the La-SA / Zn negative electrode sheet prepared in Example 1 of the present invention and the comparative blank Zn negative electrode before and after the reaction at the same scale; wherein (a) is a scanning electron microscope photograph of the pure Zn negative electrode before the reaction; (b) is a scanning electron microscope photograph of the La-SA / Zn negative electrode before the reaction; (c) is a scanning electron microscope photograph of the pure Zn negative electrode after the reaction; and (d) is a scanning electron microscope photograph of the La-SAZn negative electrode after the reaction.

[0023] Figure 2 The symmetrical battery obtained in Application Example 1 of the present invention and Comparative Application Example 1 has a capacitance of 1 mAh cm -2 2 mA cm -2 Cycling performance diagram at current density of .

[0024] Figure 3 The symmetrical battery of Application Example 1 of the present invention and Comparative Application Example 1 has a capacity of 1 mAh cm -2 , current density is 2 mA cm -2 Cycle performance diagram.

[0025] Figure 4 This is the zinc ion migration test of the La-SA / Zn negative electrode and the pure zinc negative electrode in Example 1 of the present invention.

[0026] Figure 5 It is a rate performance diagram of the symmetrical battery in Application Example 1 of the present invention and Comparative Application Example 1 at different current densities.

[0027] Figure 6 The symmetrical battery prepared in Application Example 1, Comparative Application Example 2 and Comparative Application Example 3 of the present invention was charged at a constant current of 2 mAcm -2 Zinc deposition / stripping performance diagram tested on the Blue Electric charge and discharge tester. DETAILED DESCRIPTION

[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Example 1 This embodiment is a method for preparing a chemically cross-linked interface layer La-SA modified zinc negative electrode (La-SA / Zn metal negative electrode), the steps are as follows: (1) Take 180 mg of lanthanum nitrate crystals and 20 mg of PVDF and mix them for 15 minutes. After grinding, add N-methylpyrrolidone to dissolve it. The addition amount is 10 mL per 2 g of the total amount of powder (total amount of binder + lanthanum phosphate). Use a 150 μm scraper to evenly coat the surface of the zinc sheet. The thickness of the zinc metal sheet itself is 100 μm, and the scraping thickness of the lanthanum metal salt coating is 50 μm. Then put it in an oven and dry it at 75°C for 5 hours to obtain a reaction carrier (i.e., a lanthanum metal salt coating-modified zinc negative electrode).

[0030] (2) The mass fraction of SA in the sodium alginate precursor solution is 2%. Stirring is carried out at room temperature for 12 h at a speed of 500 rpm to obtain a transparent, bubble-free precursor solution.

[0031] (3) Use a 250 μm scraper to evenly coat the precursor solution on the reaction carrier of step (1), wherein the lanthanum metal salt coating becomes thinner after drying, and is instantly absorbed by the sodium alginate solution after the sodium alginate solution precursor is scraped, and the coating thickness of the sodium alginate solution precursor is 150 μm, and then put it into a 55°C oven for drying for 8 hours. A La-SA / Zn metal negative electrode is obtained.

[0032] Example 2 This embodiment provides a La 3+ The preparation method of the zinc electrode modified with the SA in-situ chemical cross-linking interface layer comprises the following steps: (1) Take 180 mg of lanthanum nitrate crystals and 20 mg of PVDF and mix them for 15 minutes. After grinding, add N-dimethylpyrrolidone to dissolve it. The addition amount is 10 mL per 2 g of the total amount of powder (total amount of binder + lanthanum phosphate). Use a 150 μm scraper to evenly coat the surface of the zinc sheet. The thickness of the zinc metal sheet itself is 100 μm, and the thickness of the lanthanum metal salt coating is 50 μm. Then put it in an oven and dry it at 55°C for 8 hours to obtain a reaction carrier.

[0033] (2) The mass fraction of SA in the precursor solution is 3%. Stirring is carried out at room temperature for 12 h at a speed of 600 rpm to obtain a transparent, bubble-free precursor solution.

[0034] (3) Using a 200 μm scraper, the precursor solution is evenly coated on the reaction carrier of step (1), wherein the lanthanum metal salt coating becomes thinner after drying and is instantly absorbed by the sodium alginate solution after the sodium alginate solution precursor is scraped. The coating thickness of the sodium alginate solution precursor is 100 μm, and then placed in a 70°C oven for 7 hours to obtain a La-SA / Zn metal negative electrode.

[0035] Example 3 In this embodiment, a zinc negative electrode modified by a metal salt coating is coated with 1% sodium alginate, and the specific preparation method steps are as follows: (1) 180 mg of lanthanum phosphate crystals and 20 mg of PVDF were mixed and ground for 15 minutes. After grinding, N-dimethylpyrrolidone was added to dissolve it. The addition amount was 10 mL per 2 g of the total amount of powder (total amount of binder + lanthanum phosphate). A 150 μm scraper was used to evenly coat the surface of the zinc sheet. The thickness of the zinc metal sheet itself was 100 μm, and the thickness of the lanthanum metal salt coating was 50 μm. The mixture was then placed in an oven and dried at 35°C for 10 h to obtain a reaction carrier.

[0036] (2) The mass fraction of SA in the precursor solution is 1%. Stirring is carried out at room temperature for 12 h at a speed of 400 rpm to obtain a transparent, bubble-free precursor solution.

[0037] (3) Using a 250 μm scraper, the precursor solution is evenly coated on the reaction carrier of step (1), wherein the lanthanum metal salt coating becomes thinner after drying and is instantly absorbed by the sodium alginate solution after the sodium alginate solution precursor is scraped. The coating thickness of the sodium alginate solution precursor is 150 μm, and then placed in a 30°C oven for drying for 10 hours to obtain a La-SA / Zn metal negative electrode.

[0038] Example 4 This embodiment is a method for preparing a chemically cross-linked interface layer La-SA modified zinc negative electrode (La-SA / Zn metal negative electrode), the steps are as follows: (1) 160 mg of lanthanum nitrate crystals and 40 mg of PVDF were mixed and ground for 15 minutes. After grinding, N-dimethylpyrrolidone was added to dissolve it. The addition amount was 10 mL per 2 g of the total amount of powder (total amount of binder + lanthanum phosphate). A 150 μm scraper was used to evenly coat the surface of the zinc sheet. The thickness of the zinc metal sheet itself was 100 μm, and the thickness of the lanthanum metal salt coating was 50 μm. The zinc sheet was then placed in an oven and dried at 55°C for 10 h to obtain a reaction carrier.

[0039] (2) The mass fraction of SA in the precursor solution is 2%. Stirring is carried out at room temperature for 12 h at a speed of 500 rpm to obtain a transparent, bubble-free precursor solution.

[0040] (3) Using a 250 μm scraper, the precursor solution is evenly coated on the reaction carrier of step (1), wherein the lanthanum metal salt coating becomes thinner after drying and is instantly absorbed by the sodium alginate solution after the sodium alginate solution precursor is scraped. The coating thickness of the sodium alginate solution precursor is 150 μm, and then placed in a 55°C oven for drying for 8 hours to obtain a La-SA / Zn metal negative electrode.

[0041] Example 5 This embodiment is a method for preparing a chemically cross-linked interface layer La-SA modified zinc negative electrode (La-SA / Zn metal negative electrode), the steps are as follows: (1) Take 160 mg of lanthanum nitrate crystals and 40 mg of PVDF and mix them for 15 minutes. After grinding, add N-dimethylpyrrolidone to dissolve it. The addition amount is 10 mL per 2 g of the total amount of powder (total amount of binder + lanthanum phosphate). Use a 150 μm scraper to evenly coat the surface of the zinc sheet, where the thickness of the zinc metal sheet itself is 100 μm and the thickness of the lanthanum metal salt coating is 50 μm. Then put it in an oven and dry it at 75°C for 4 hours to obtain a reaction carrier.

[0042] (2) The mass fraction of SA in the precursor solution is 1%. Stirring is carried out at room temperature for 12 h at a speed of 400 rpm to obtain a transparent, bubble-free precursor solution.

[0043] (3) Use a 150 μm scraper to evenly coat the precursor solution on the reaction carrier of step (1), wherein the lanthanum metal salt coating becomes thinner after drying, and is instantly absorbed by the sodium alginate solution after the sodium alginate solution precursor is scraped, and the coating thickness of the sodium alginate solution precursor is 50 μm, and then put it into a 30° oven for drying for 10 hours. A La-SA / Zn metal negative electrode is obtained.

[0044] Example 6 This embodiment is a method for preparing a chemically cross-linked interface layer La-SA modified zinc negative electrode (La-SA / Zn metal negative electrode), the steps are as follows: (1) Take 160 mg of lanthanum nitrate crystals and 40 mg of PVDF and mix them for 15 minutes. After grinding, add N-dimethylpyrrolidone to dissolve it. The addition amount is 10 mL per 2 g of the total amount of powder (total amount of binder + lanthanum phosphate). Use a 150 μm scraper to evenly coat the surface of the zinc sheet, where the thickness of the zinc metal sheet itself is 100 μm and the thickness of the lanthanum metal salt coating is 50 μm. Then put it in an oven and dry it at 75°C for 6 hours to obtain a reaction carrier.

[0045] (2) The mass fraction of SA in the precursor solution is 3%. Stirring is carried out at room temperature for 12 h at a speed of 600 rpm to obtain a transparent, bubble-free precursor solution.

[0046] (3) Using a 200 μm scraper, the precursor solution is evenly coated on the reaction carrier of step (1), wherein the lanthanum metal salt coating becomes thinner after drying and is instantly absorbed by the sodium alginate solution after the sodium alginate solution precursor is scraped. The coating thickness of the sodium alginate solution precursor is 100 μm, and then placed in a 70° oven for drying for 7 hours to obtain a La-SA / Zn metal negative electrode.

[0047] Comparative Example 1 This comparative example provides a method for preparing a zinc negative electrode, wherein a sodium alginate-modified zinc negative electrode (SA / Zn metal negative electrode) is prepared by coating a zinc negative electrode sheet with SA only, and the steps are as follows: (1) The mass fraction of SA in the precursor solution is 2%. Stirring is carried out at room temperature for 12 h at a speed of 600 rpm to obtain a transparent, bubble-free precursor solution.

[0048] (2) The precursor solution was evenly coated on the reaction carrier with a coating thickness of 200 μm, and then placed in a 75°C oven for drying for 5 hours to obtain a SA / Zn metal negative electrode.

[0049] Comparative Example 2 This comparative example provides a method for preparing a zinc negative electrode, wherein only a lanthanum metal salt is used to coat a zinc negative electrode sheet to prepare a lanthanum metal salt-modified zinc negative electrode (denoted as La 3+ / Zn metal anode), the steps are as follows: 160 mg of lanthanum nitrate crystals and 40 mg of PVDF were mixed and ground for 15 minutes. After grinding, N-dimethylpyrrolidone was added to dissolve it. The addition amount was 10 mL per 2 g of the total amount of powder (total amount of binder + lanthanum phosphate). The zinc sheet was evenly coated with a 200 μm scraper and then placed in a 75 ° C oven for 5 hours to obtain a lanthanum metal salt modified zinc negative electrode (referred to as La 3+ / Zn metal anode).

[0050] Application Examples 1-6 This application example provides an application of a cross-linked interface layer La-SA / Zn metal negative electrode in an aqueous zinc ion battery, as shown below: Aqueous zinc sulfate electrolyte was used, glass fiber was used as a separator, and the cross-linked interface layer La-SA / Zn metal negative electrodes prepared in Examples 1-6 were used as electrode sheets to assemble La-SA / Zn / / La-SA / Zn symmetric batteries, corresponding to Application Examples 1-6, respectively, specifically: The La-SA / Zn metal electrodes prepared in Examples 1-6 were punched into discs with a diameter of 8 mm, respectively. Glass fiber was used as a separator, 2 M ZnSO4 solution was used as an electrolyte, and metal gaskets and springs were used as filling materials to assemble CR-2032 button-type La-SA / Zn / / La-SA / Zn symmetrical batteries, corresponding to Application Examples 1-6, respectively. The batteries were packaged using a packaging machine and then left to stand for 7 h before the electrochemical performance test was performed.

[0051] Comparative application example 1 The method for preparing a battery described in Application Examples 1-6 was adopted to assemble a CR-2032 type button-type zinc / / zinc symmetrical battery using pure zinc as an electrode sheet.

[0052] Comparative Application Example 2 In this comparative application example, the battery is prepared by the method described in Application Examples 1-6, and the SA / Zn metal electrode prepared in Comparative Example 1 is used as the electrode sheet to assemble a CR-2032 type button-type SA / Zn / / SA / Zn symmetrical battery.

[0053] Comparative Application Example 3 This comparative application example adopts the method described in application example 1 to prepare a battery, and compares the La prepared in example 2. 3+ / Zn metal electrode was used as the electrode sheet and assembled into CR-2032 type button type La 3+ / Zn / / La 3+ / Zn symmetrical battery.

[0054] Battery performance analysis 1. Coating stripping performance test analysis: The SEM comparison of the La-SA / Zn electrode and the pure zinc negative electrode before and after zinc electroplating / stripping of Example 1 is shown in FIG. Figure 1 shown. Figure 1 (a) is the SEM image of the pure Zn electrode before the reaction; (b) is the SEM image of La-SA / Zn before the reaction; (c) is the SEM image of the pure Zn electrode after the reaction; (d) is the SEM image of La-SA / Zn after the reaction. From (a) and (b), it can be seen that the surface of the pure Zn comparison sample before the reaction is relatively flat, and from (b), it can be seen that the surface morphology of the prepared La-SA / Zn is flat and uniform; from (c), it can be seen that the surface of the blank pure Zn is uneven after the reaction, and many vertical dendrite byproducts appear. In severe cases, the dendrites will pierce the diaphragm and cause battery damage. However, from (d), it can be seen that the surface of the electrode sheet of the nanoparticle La-SA / Zn maintains its original uniform distribution morphology after cycling, and there is no zinc dendrite deposition on the surface. It can be seen that La-SA modification can also inhibit the growth of zinc dendrites and avoid the formation of vertical zinc dendrites.

[0055] 2. Electrochemical performance test analysis: Figure 2 and Figure 3 This is a performance comparison chart of the La-SA / Zn / / La-SA / Zn symmetrical battery prepared in Application Example 1 of the present invention and the Zn / / Zn symmetrical battery prepared in Comparative Application Example 1. Figure 2 , 3 shows that at 1 mA cm -2 and 2 mA cm -2 At a current density of 2.5, when the Zn / / Zn battery of Example 1 was cycled for less than 80 h, its polarization voltage curve dropped drastically, indicating that the symmetrical battery was short-circuited and damaged. In contrast, the La-SA / Zn symmetrical battery of Example 1 still showed a stable polarization voltage curve after 1400 h of cycling, showing excellent cycling stability. Figure 5It can be seen that when the current density is switched, the pure zinc negative electrode will experience a sudden change in polarization voltage or a short circuit. On the contrary, for the La-SA / Zn / / La-SA / Zn battery of Application Example 1, when the current density is switched from 1 to 10 mA cm -2 When the polarization curve changes from 10 mA cm -2 Switch back to 1 mA cm -2 When the La-SA / Zn / / La-SA / Zn symmetric battery of Application Example 1 is charged, the polarization voltage can still be kept stable, which indicates that La-SA / Zn has excellent rate performance.

[0056] 3. Zinc ion migration test (CA): The La-SA / Zn electrode sheet prepared in Example 1 was subjected to CA and negative electrode zinc ion migration number tests to characterize the excellent performance of the La-SA / Zn electrode sheet in enhancing ion diffusion kinetics during zinc ion deposition, such as Figure 4 As shown. Figure 4 The CA diagram shows that La-SA / Zn quickly achieves uniform three-dimensional diffusion of zinc ions, while the two-dimensional diffusion process of zinc ions in pure Zn is very long. Long two-dimensional diffusion easily leads to the growth of dendrites, indicating that its deposition mechanism is unsatisfactory.

[0057] 4. Assembly and testing of Zn / / Zn symmetrical cells The La-SA / Zn / / La-SA / Zn symmetric battery of Application Example 1, the SA / Zn / / SA / Zn symmetric battery of Comparative Application Example 2, and the La 3+ / Zn / / La 3+ / Zn symmetric cell, using constant current method 2 mA cm -2 The zinc deposition / stripping performance was tested on a blue electric charge and discharge tester to characterize its cycling performance and polarization potential. The results are shown in Figure 6 The battery cycle performance of the batteries of application examples 1-6 and comparative application example 1 and comparative application example 2 are shown in Table 1: As can be seen from Table 1, compared with Application Example 1, the SA ratio in Application Example 2 is reduced, and the coating on the electrode surface falls off after 600 hours of circulation. Compared with Application Example 1, the SA ratio in Application Example 3 is reduced, and the thickness of the cross-linking interface is greatly reduced. The bottom layer cannot react and is more likely to fall off. Compared with Application Example 1, the binder in Application Example 4 is increased. Although the surface bonding performance is increased, the binder sinks to the bottom, resulting in the failure of the cross-linked layer after the reaction to completely adhere to the metal surface. The life is reduced compared with Example 1. In Application Example 5, the gel layer is too thin due to the increase of the binder, and the life is drastically reduced compared with Example 1. In Application Example 6, the cross-linked layer is thinned due to the increase of the binder, and the life is reduced compared with Example 1. Compared with Application Example 2, since no cross-linked surface layer is formed at the beginning, a large amount of it falls off during the cycle. Compared with Application Example 3, since the lanthanum salt is soluble in water, it dissolves directly, which is no different from ordinary zinc anodes and has an extremely short life.

[0058] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a zinc negative electrode modified with an in-situ chemical cross-linking interface layer, characterized in that: The preparation steps are as follows: (1) fully grinding and mixing a lanthanum metal salt and a binder, uniformly coating the mixed powder obtained by grinding on the surface of a zinc negative electrode with the aid of an organic solvent, and drying to obtain a zinc negative electrode modified with a lanthanum metal salt coating; (2) The sodium alginate aqueous solution precursor is uniformly coated on the zinc negative electrode sheet modified with the lanthanum metal salt coating, and after drying, a zinc negative electrode modified with an in-situ chemical cross-linked interface layer containing lanthanum ions and sodium alginate is obtained.

2. The method for preparing a zinc negative electrode modified with an in-situ chemical cross-linking interface layer according to claim 1, characterized in that: In step (1), the metal salt of lanthanum is one or more of lanthanum nitrate, lanthanum chloride and lanthanum acetate; the binder is polyvinylidene fluoride or polytetrafluoroethylene, and the organic solvent is N-methylpyrrolidone.

3. The method for preparing a zinc negative electrode modified with an in-situ chemical cross-linking interface layer according to claim 2, characterized in that: In the step (1), the mass ratio of the lanthanum metal salt to the binder is (9-4):

1.

4. The method for preparing a zinc negative electrode modified with an in-situ chemical cross-linking interface layer according to claim 1, characterized in that: The thickness of the lanthanum metal salt coating on the zinc negative electrode sheet in step (1) is 50-100 μm.

5. The method for preparing a zinc negative electrode modified with an in-situ chemical cross-linking interface layer according to claim 1, characterized in that: The drying temperature in step (1) is 35-75° C. and the drying time is 4-10 hours.

6. The method for preparing a zinc negative electrode modified with an in-situ chemical cross-linking interface layer according to claim 1, characterized in that: The concentration of the sodium alginate aqueous solution in step (2) is 10-30 mg mL -1 .

7. The method for preparing a zinc negative electrode modified with an in-situ chemical cross-linking interface layer according to claim 1, characterized in that: In the step (2), the thickness ratio of the sodium alginate coating to the lanthanum metal salt coating is (1-3):

1.

8. The method for preparing a zinc negative electrode modified with an in-situ chemical cross-linking interface layer according to claim 1, characterized in that: In the step (2), the drying temperature is 30-70° C. and the drying time is 7-10 h.

9. A zinc negative electrode modified with an in-situ chemical cross-linking interface layer prepared by the method according to any one of claims 1 to 8.

10. Use of the zinc negative electrode modified with the in-situ chemical cross-linking interface layer as claimed in claim 9 in an aqueous zinc-based energy storage device.